The Clash of Civilisations? Religion as a Major Component of Cultural Differentiation on the Example of Belarus and Poland - Pieczewski, Andrzej; Sidarava, Aliaksandra (Comparative Economic Research. Central and Eastern Europe, 2025)
This comparative study investigates the role of religion as an important factor in shaping political and economic mental models, focusing on the contexts of Belarus and Poland. It builds upon Samuel Huntington’s thesis, which posits that cultural and religious differences are fundamental to civilisational conflicts. By analysing how Catholicism and Orthodoxy have shaped the divergent mentalities of these neighbouring nations, this research highlights the long-lasting influence of religious traditions on societal development. Employing a mixed-methods approach, including CATI surveys, statistical analyses, and historical comparisons, the study identifies significant differences in political and economic behaviours between Belarusians and Poles. These disparities underline the long-term impact of religion on attitudes toward power, property, and individualism. The findings contribute to a nuanced understanding of how religious values not only define societal norms but also shape national trajectories and contemporary geopolitical alignments. This research underscores the enduring relevance of religion in explaining cultural dynamics and civilisational divides in Eastern Europe.